Clinical significance of serum tumor markers for advanced gastric cancer with the first-line chemotherapy - Sun, Zhiwei; Jia, Jun; Du, Feng; Yang, Ying; Liu, Chuanling; Xiao, Yanjie; Yu, Jing; Zhang, Xiaodong (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: Tumor markers play an important role in the diagnosis, monitoring and prognostic prediction of cancers. But the predictive value of serum tumor markers in gastric cancer is still unclear. Methods: In this study, we detected serum levels of tumor markers to evaluate their relation to treatment response and prognosis in patients with unresectable advanced or metastatic gastric cancer. Results: We collected the clinical data of 109 patients with unresectable advanced or metastatic gastric cancer who had received the first-line chemotherapy in Peking University Cancer Hospital from July 2013 to May 2015, and collected the value of serum carcinoembryonic antigen (CEA), carbohydrate antigen 199 (CA199), carbohydrate antigen 72.4 (CA72.4) and carbohydrate antigen 125 (CA125) before and after chemotherapy. At diagnosis, the positive rates of CEA, CA199, CA72.4 and CA125 were 46.8%, 40.2%, 53.5% and 35.0%, respectively. And the positive rate of combined detection of the four markers was 87.2%. Although patients with prechemotherapy CA199 ≥80 U/mL (92.3% vs. 68.5%, P=0.016) or CA72.4 ≥20 U/mL (91.4% vs. 62.5%, P=0.003) had higher clinical benefit rate after chemotherapy, they showed poorer prognosis (P=0.023 and P=0.006, respectively). CA72.4 ≥20 U/mL was an independent unfavorable prognostic factor (Hazard Ratio 4.84; 95% confidence interval: 1.910–12.262; P=0.001). In patients with increased levels of tumor markers before treatment, the levels of tumor markers decreased after chemotherapy, especially in those with clinical benefit (CEA, CA72.4 reached statistical significance, P=0.013 and P=0.029, respectively). A decrease of CEA ≥35%, CA199 ≥30%, or CA72.4 ≥40% after chemotherapy had positive prediction value for the response to chemotherapy (P=0.016, P=0.029, and P=0.008, respectively). Conclusions: The results showed that both high pre-chemotherapy serum levels of tumor markers (CA199 ≥80 U/mL or CA72.4 ≥20 U/mL) and a substantial decrease in tumor markers after chemotherapy (CEA ≥35%, CA199 ≥30%, or CA72.4 ≥40%) could predict a higher clinical benefit rate in patients with unresectable advanced or metastatic gastric cancer. However, this advantage in short-term response to chemotherapy failed to convert into prolonged survival benefits.